PENAMBATAN MOLEKULER SENYAWA CENDAWAN ENDOFIT Trichoderma sp. SEBAGAI INHIBITOR PROTEIN LOW DENSITY LIPOPROTEIN, ENZIM LANASTEROL 14 DEMETILASE DAN LIPASE YANG BERTANGGUNG JAWAB DALAM DERMATITIS SEBOROIK - Eka Sukmawaty; Susi Susanti; Masriany Masriany Masriany (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Seborrheic dermatitis (SD) occurs due to excessive sebum production resulting in the growth of the fungus Mellasezia sp. on the skin becomes uncontrollable. Some of the receptors that play a role in SD regulation are Low Density Lipoprotein (LDL) protein, Lanasterol 14-Î± Demetylase enzyme, and Lipase enzyme. This study aims to determine the potential compounds of the endophytic fungi Trichoderma sp. as an antiseborrheic and knowing the interaction between ligands as inhibitors in SD regulation. The research was conducted with computer-based molecular docking. The results showed that there were two inhibitor candidate compounds based on the selection by binding affinity value, namely Chloromycetin and Benzyl benzoate. Based on the results of docking with VINA autodock, the potential compounds were Benzyl benzoate on LDL protein with binding affinity values of -7.3 kcal/mol, compounds were Chloromycethin on Lipase enzyme with binding affinity values of -7.3 kcal/mol and Lanasterol 14-Î± demethylase enzyme with a binding affinity value of -7.6 kcal/mol. These compounds form hydrogen bonds and hydrophobic bonds. Based on the prediction of Lipinski's rule of five, the two compounds are effective orally used as anti seborrheic dermatitis drugs